The Limits of Dewey’s Philosophy: Cultural Historical Activity Theory and Experience - Sangok Park; Fred M. Schied (Adult Education Research Conference, 2007)
This paper argues that activity theory, specifically cultural historical activity theory (CHAT), has explored the concepts of mediation, tools, signs, and appropriation as a means to overcome the inherent dualism in Dewey’s theory of experience and learning.